Participatory Budget as a Form of Social Participation: The Example of Communes in Poland in 2020–2022 - Perska, Anita; Stefańska, Magdalena (Journal of Public Governance, 2024)
Objective: In the process of managing a commune, the needs of the community inhabiting the area of a given commune are met, and the commune budget constitutes the basis of the commune’s financial management. The commune budget is an annual plan of income and expenses as well as the commune’s revenues and expenditures. Communes enable the residents to decide how to spend part of the budget in the form of a participatory budget. The aim of this article is to identify and assess the activity of various types of communes in the field of participatory budget planning in Poland, as well as to explain the reasons behind differences in the level of the commitment. Research Design & Methods: Selected literature references in the subject scope of the article are analysed. In addition, an analysis of secondary data was performed regarding the number of communes with a planned amount of participatory budget. The analysis is conducted considering the criterion of the type of commune (rural, urban, rural-urban). The time scope of the analysis covers the years 2020–2022. Findings: The share of communes that invite inhabitants to participate in the decision-making process on how to spend part of public money as participatory budget is quite low. In the years 2020–2022, 12.27%, 11.18%, and 12.92% of all communes in Poland planned a participatory budget. In 2021, compared to 2020, there was a smaller number of communes that had a planned participatory budget. This could be due to the COVID-19 pandemic that had been ongoing since 2020. The level of offering communities the participation in the decision-making process differs in various types of communes, and that differentiation is statistically valid. Since the sources of such differences mainly can come from social, cultural, economic, or political reasons, they were explored more deeply. Implications / Recommendations: Due to the diversity of the types of communes in terms of population, it is recommended that an analysis be conducted according to the discussed determinants. The results may be helpful for local managers in terms of including them into the local sustainable strategy participatory budget instrument and following Sherry Arnstein’s (2019) ladder process while considering local constraints and opportunities. Contribution / Value Added: The exploration of participatory budget mostly concentrated on larger urban communes. However, the delved analysis of the implementation of participatory budget in rural or rural-urban communes was not so popular. The added value is the analysis according to the type of communes as well as the discussion on the reasons behind such differences. The paper contributes to the discussion of the stimulators and inhibitors of the implementation of such a tool in creating locally social capital and tightening relations among different stakeholders in the name of common good. Article classification: research article JEL classification: H7, O2, R5